Analysis of Hydrodynamic Patterns and Suspended Sediment Transport in the Virrila Estuary-Peru - Yoch, P (2018)
This work is part of the Treatment/remediation and recovery of bays project using innovative procedures project led by CITBM and funded by the National Science, Technology and Technological Innovation Council (CONCYTEC in spanish) through the program CIENCIACTIVA. Thanks to Water Research Center CITA-UTEC for the support with the instrumentation for the measurements campaign; Tobias Bleninger and Julio Werner for background and feedback, Carlos Landauro, Justiniano Quispe and César Aguirre for the administrative and logistical support in the measurements. Thanks to Hugo Montoro, Tania Rojas, Mishel Meléndez, and Sofía Valdivia for the support with information processing. Thanks to Herver Caruzo, Elivorio Castillo for the support in the measurements and the transportation of equipment